ICT Based Project in Learning Basic Airplane Components - Maria Asumpta deny Kusumaningrum; Dewanti Ratna Pertiwi (Jurnal Pendidikan Bahasa, 2021)
In this era, preparing the students for the 21st century is one of the demands in education which is using ICT in the learning activity. With all the skills that are required, the students are expected to be able to compete in the global marketplace in the future. Working in a team is also important thing to train for the students in this era. This research focuses on using ICT based project in teaching activity especially in learning basic airplane components. The research involved 40 students with two classes of the year 2019. This research will answer two research questions which are (1) What are the students’ perception of the benefits on the implementation of ICT supported PBL to the language skill development? and (2) What are the students’ perceptions of the benefits on implementation of ICT supported PBL to the self-development? This research applied a case study. The instruments used to support this research were the researcher as the main instrument, a questionnaire and the students reports. The implementation of ICT brings the positive learning environment where the students participate to develop their knowledge and skill process.